2018
DOI: 10.1093/nar/gky787
|View full text |Cite
|
Sign up to set email alerts
|

Global landscape of mouse and human cytokine transcriptional regulation

Abstract: Cytokines are cell-to-cell signaling proteins that play a central role in immune development, pathogen responses, and diseases. Cytokines are highly regulated at the transcriptional level by combinations of transcription factors (TFs) that recruit cofactors and the transcriptional machinery. Here, we mined through three decades of studies to generate a comprehensive database, CytReg, reporting 843 and 647 interactions between TFs and cytokine genes, in human and mouse respectively. By integrating CytReg with o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 81 publications
1
44
0
Order By: Relevance
“…Secondly, we further used a set of 113 human cytokines to quantify host inflammation responses between three viruses. The 113 cytokines from the CytoReg database were often cited by various publications and play a primary role in the immune system [25].…”
Section: Mers-covmentioning
confidence: 99%
“…Secondly, we further used a set of 113 human cytokines to quantify host inflammation responses between three viruses. The 113 cytokines from the CytoReg database were often cited by various publications and play a primary role in the immune system [25].…”
Section: Mers-covmentioning
confidence: 99%
“…Research conducted for more than three decades has identified 170 TFs that bind to the transcriptional control regions and/or regulate 95 (of ~140) human cytokine genes (Carrasco Pro et al, 2018). This includes TFs that are activated by pathogen signals (e.g., NF-κB, AP-1, and IRFs), stress signals (e.g., HIF1A, TP53, and HSF1), cytokine signals (e.g., STATs and NF-κB), as well as lineage factors (e.g., SPI1 and CEBPA).…”
Section: Introductionmentioning
confidence: 99%
“…However, analysis of this literature-derived human cytokine protein-DNA interaction (PDI) network suggests that this network is largely incomplete. For instance, no PDIs have been reported for nearly 30% of the cytokine genes, and new TFs and PDIs in the cytokine PDI network are still being reported at a rate of 6.6 TFs and 35 PDIs per year (Carrasco Pro et al, 2018). More importantly, most PDIs reported in the literature correspond to highly studied TFs and cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…we suspected that under conditions of GGTase inhibition, expression of a transcription factor necessary for IL-10 may be compromised. To test this, we performed RNA-sequencing on TLR9- have been shown to regulate IL-10 expression in other cell types ( Figure 5B-D, Supplementary Figure 7C), either through activation or repression (defined in 30 ). We decided to focus on BLIMP1 for two reasons.…”
mentioning
confidence: 99%